Design and Feasibility Analysis of a Dual Operation Mode Hybrid Mechanism - Xinglu Yin; Chunyan Zhang; Mingjuan Xie (Jixie chuandong)
Serial and parallel configurations are mutually exclusive in performance and structure， this prevents performance advantages from being combined. To solve this problem， a novel hybrid configuration which can realize serial and parallel switching based on a motion bifurcation mechanism is proposed， and a reconfigurable dual operation manipulator is designed. The structure of the new manipulator is introduced， the degrees of freedom under each configuration of the reconfigurable manipulator are analyzed， and the characteristics of degrees of freedom of 3-RSR/S parallel base are analyzed by using screw theory. By comparing the constrained screw systems with the adjacent configurations of the reconfigure manipulators， the feasibility analysis is carried out. According to the motion characteristics of the manipulator in different modes， based on the control theory of CPG (central pattern generator)， the multi-mode control and mode switching are realized， the feasibility of the manipulator mode switching is verified by simulation experiments. The results show that the design scheme is reasonable and feasible， and the further prototype model design is completed. The new configuration is a new attempt in the innovation and development of complex advanced equipment， and can be extended to the special working conditions with more station properties.